Congenital adrenal hyperplasia is a very rare cause of adrenal incidentalomas in Sweden - Sahlander, Fredrik; Bensing, Sophie; Falhammar, Henrik (Frontiers in Endocrinology, 2022)
Background: Undiagnosed congenital adrenal hyperplasia (CAH) can cause adrenal incidentalomas but the frequency is unclear. Objectives: To investigate the prevalence of CAH in a population with adrenal incidentalomas and report the clinical characterization. Material and methods: This was a prospective study performed at a regional hospital 2016-2021. Patients with adrenal incidentalomas was investigated with an ACTH-stimulation test in addition to hormonal work-up. Serum cortisol and 17-hydroxyprogesterone (17OHP) was analyzed. Individuals with a basal or stimulated 17OHP ≥30 nmol/L were classified as suspicious non-classic CAH and a CYP21A2-gene analysis was performed in these subjects. Results: In total 320 individuals with adrenal incidentalomas were referred to the center and of these an ACTH-stimulation test was performed in 222 individuals (median age 67 (24-87) years, 58.6% women and 11.7% with bilateral lesions). None of the individuals presented a basal 17OHP ≥30 nmol/L, but 8 (3.6%) after ACTH-stimulation. Four of these subjects (50%) presented bilateral lesions and the tumor size was larger compared to individuals with a stimulated 17OHP <30 nmol/L (median 38 (19-66) vs 19 (11-85) mm, p=0.001). A CYP21A2-variation (p.Val282Leu) was detected in one of the 8 subjects (12.5%) with a stimulated 17OHP ≥30 nmol/L, i.e., the patient was a heterozygotic carrier. None of the 8 subjects presented with cortisol insufficiency or clinical signs of hyperandrogenism. Conclusions: The prevalence of non-classic CAH in an adrenal incidentaloma cohort was 3.6% based on stimulated 17OHP and zero percent based on gene analysis. Despite this, CAH should be considered in the management of adrenal incidentalomas.